Analisis Pengaruh Harga, Promosi, Dan Distribusi Terhadap Volume Penjualan Batu Split (Stone Crusher) Pada Cv. SehatiDi Tirtomoyo Wonogiri - Sari, Anggraini Fitria (2016)
The purpose of this study is to analyze the effect of pricing, promotion, and distribution, whether it is carried out partially or simultaneously, to sales volume of split stone and the dominant variable in influencing sale volumes at CV. Sehati Tirtomoyo Wonogiri. The methodology which is used in this research is descriptive quantitative research methodology, where the conclusions is drawn from statistical approach. The object of study in this research were 100 customers of CV. Sehati Wonogiri, whom I chose using convenience sampling, and I used primary source from questionnaire. The data analysis technique which is used here is multiple linear regression analysis, F expriment, T expriment, and expriment of coefficient of determination. Before those experiments were taken, I did perfore classical assumption experiments in the form of normality, multicollinearity, and heteroscedasticity experiment. The results showed that: 1) The price, promotion, and distribution of partially significant effect on sales volume CV. Sehati. This is evident from the results of t-test to obtain t count 5.932 for the variable price; t count 4.61 for the variable promotion, and count 5.835 for the variable distribution, are all accepted at the significant level of 5% (p <0.05); 2) The price, promotion, and distribution simultaneously significant effect on sales volume CV. Sehati. This is evident from the results of the F test that received F count of 44.179 accepted at significance level of 5% (p <0.05). Results of multiple regression analysis to obtain multiple regression equation to obtain the following regression equation: Y = 9.183 + 0,272.X1 + 0,322.X2 + 0,234.X3. The equation shows that the volume of sales affected by pricing, promotion, and distribution; 3) The price gives a dominant influence on the sales volume due t count welfare variable is the biggest (5.932). That meaning the sales volume will increase if the employee has a high price.